Maternal and Child Health nurse's preparedness to respond to women and children experiencing intimate partner violence: A cross sectional study. (January 2021) - Hooker, Leesa; Nicholson, Jan; Hegarty, Kelsey; Ridgway, Lael; Taft, Angela
Abstract: Background: Intimate partner violence victims regularly seek health care and support. Health care providers need to understand the complexities of partner violence and how to safely respond to clients. Policy guiding nurse identification and responses exist, yet practices and education are lagging. Maternal and Child Health nurses are required to address intimate partner violence, yet their knowledge and preparedness to undertake this work is under-explored. The most effective methods of provider training are unknown. Objectives: 1) To assess the level of Maternal and Child Health nurse intimate partner violence training and nurse preparedness to address partner violence and 2) compare group differences in preparedness by nurse location, role and level of training. Design: A cross sectional research design. Participants: Australian community based Maternal and Child Health nursing workforce. Methods: Online survey conducted in June 2018. Survey questions explored nurse characteristics, knowledge and 'preparedness' to complete intimate partner violence work and previous violence training. Descriptive analysis involved reporting proportions within categories. Proportional group differences were analysed using Chi square test of independence. Statistical significance was set at p < 0.05. Results: Survey response rate was 65% (735/1125). Nurses feel well prepared to complete intimate partner violence practices, although differences were seen across groups. Rural nurses feel less prepared than metropolitan colleagues, especially conducting safety assessments and documentation. Nurse co-ordinators are the most prepared. A dose response relationship is seen between training and preparedness: nurses with greater (>10 h) and more recent training (within 5 years) report being more prepared for intimate partner violence work. Conclusions: Greater systems supports are needed for sustainable nurse intimate partner violence work. In particular, opportunities are needed for rural nurse training, delivered locally and tailored to rural needs and context. Nurse co-ordinators are key leaders to achieving sustained nurse intimate partner violence practices. Highlights: Maternal and Child Health nurses routinely ask all women about intimate partner violence. Nurse education and skill development on intimate partner violence is limited. Frequent training enhances preparedness to identify and support women experiencing partner violence. Rural nurses have less violence training, feel less prepared and need more support. Coordinators hold leadership roles that are key to sustained practice change.